Persistent iodine deficiency in a cohort of Tasmanian school children: associations with socio‐economic status, geographical location and dietary factors - Kristen L. Hynes; C. Leigh Blizzard; Alison J. Venn; Terence Dwyer; John R. Burgess (Australian and New Zealand Journal of Public Health, 2004)
Abstract Objective: To determine the adequacy of iodine nutrition of Tasmanian primary school‐aged children and to examine possible associations with socio‐economic status (SES), location and dietary factors. Methods: Urinary iodine levels and measures of SES, geographical information and dietary habits were surveyed in a population‐based sample of 170 children (4 to 12 years) at baseline (1998/99) and at follow‐up (2000/01). Results: Median urinary iodine concentration in 1989‐99 and 2000‐01 were 75 μg/L (range 15 μg/L to 240 μg/L) and 76 μg/L (range 18 μg/L to 480 μg/L) respectively. No significant associations with SES or geographical location were found. More frequent or recent intake of foods that are likely to be dietary sources of iodine tended to be associated with greater prevalence of adequate urinary iodine, particularly consumption of yoghurt and ‘fruche’ (p=0.04). Conclusions: After several decades of iodine sufficiency, Tasmanian primary school‐aged children are again mildly iodine‐deficient by WHO criteria. Despite reduction in iodophor use by the dairy industry in the past decade, consumption of dairy products continues to be associated with higher levels of iodine nutrition. Implications: The lack of association of iodine levels with SES and geographical location within Tasmania found in our study, and the results of studies of iodine levels in Melbourne and Sydney, suggest that inadequate iodine nutrition is a widespread problem in south‐eastern Australia. Our study suggests that milk‐containing products continue to be an important source of iodine for children.